Detailed Transmission Network Analysis of a Large Opiate-Driven Outbreak of HIV Infection in the United States. (5th October 2017) - Campbell, Ellsworth M; Jia, Hongwei; Shankar, Anupama; Hanson, Debra; Luo, Wei; Masciotra, Silvina; Owen, S Michele; Oster, Alexandra M; Galang, Romeo R; Spiller, Michael W; Blosser, Sara J; Chapman, Erika; et al.
Abstract : We demonstrate that integration of laboratory, phylogenetic, and epidemiologic data sources allow detailed reconstruction of an outbreak. High-resolution reconstruction of outbreak phylodynamics allows prevention and intervention strategies to be tailored to community needs. Abstract: In January 2015, an outbreak of undiagnosed human immunodeficiency virus (HIV) infections among persons who inject drugs (PWID) was recognized in rural Indiana. By September 2016, 205 persons in this community of approximately 4400 had received a diagnosis of HIV infection. We report results of new approaches to analyzing epidemiologic and laboratory data to understand transmission during this outbreak. HIV genetic distances were calculated using the polymerase region. Networks were generated using data about reported high-risk contacts, viral genetic similarity, and their most parsimonious combinations. Sample collection dates and recency assay results were used to infer dates of infection. Epidemiologic and laboratory data each generated large and dense networks. Integration of these data revealed subgroups with epidemiologic and genetic commonalities, one of which appeared to contain the earliest infections. Predicted infection dates suggest that transmission began in 2011, underwent explosive growth in mid-2014, and slowed after the declaration of a public health emergency. Results from this phylodynamic analysis suggest that the majority of infections had likely already occurred when the investigation began and that early transmission may have been associated with sexual activity and injection drug use. Early and sustained efforts are needed to detect infections and prevent or interrupt rapid transmission within networks of uninfected PWID.